2020
DOI: 10.5507/ag.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

Playing position specifics of associations between running performance during the training and match in male soccer players

Abstract: Thus, proper and continuous monitoring of the training load is important to determine the applied training load and implement interventions in subsequent sessions (i.e., increases or decreases in the training load; Jaspers et al., 2017; Rebelo et al., 2012). Training loads can comprise external and internal loads (Impellizzeri, Rampinini, Coutts, Sassi, & Marcora, 2004). External training loads are measured by the work done by players and are currently commonly monitored by Global Positioning System (GPS) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Taking into account the above discussed influence of ANAT on high-intensity distance covered (high-speed running and sprinting), it seems that forwards in their training methodology probably do not have enough training stimuli to enable them to develop their AT. Similarly, previous studies have reported that forwards' training drills are based on short-intensity efforts (high-intensity accelerations and decelerations þ shooting) rather than sprinting [31]. All of these factors together (e.g., tactical roles in game and training style) probably resulted in a relatively low level of AF in forwards.…”
Section: Differences In Aerobic Fitness Among Playing Positionsmentioning
confidence: 65%
See 1 more Smart Citation
“…Taking into account the above discussed influence of ANAT on high-intensity distance covered (high-speed running and sprinting), it seems that forwards in their training methodology probably do not have enough training stimuli to enable them to develop their AT. Similarly, previous studies have reported that forwards' training drills are based on short-intensity efforts (high-intensity accelerations and decelerations þ shooting) rather than sprinting [31]. All of these factors together (e.g., tactical roles in game and training style) probably resulted in a relatively low level of AF in forwards.…”
Section: Differences In Aerobic Fitness Among Playing Positionsmentioning
confidence: 65%
“…One of the most important tactical roles of forwards is to keep the ball in possession in the central position; therefore, it is expected that forwards do not cover a large distance [3]. Additionally, it has been reported that forwards are actually undertrained in terms of sprint distance covered through weekly training sessions, which means that they do not experience large amounts of sprint distance in training sessions [31]. Taking into account the above discussed influence of ANAT on high-intensity distance covered (high-speed running and sprinting), it seems that forwards in their training methodology probably do not have enough training stimuli to enable them to develop their AT.…”
Section: Differences In Aerobic Fitness Among Playing Positionsmentioning
confidence: 99%
“…Soccer (football) is a sport that requires excellent tactical, technical, and physical performance skills (Hoff et al, 2002). It is known that elite soccer players can cover 9-14 km of total distance during a soccer match (Bekris et al, 2020;Merlin et al, 2020;Milanović et al, 2017;Modric et al, 2020b). However, elite soccer players spend the majority of match play performing low-intensity activities (e.g., standing, walking, jogging), while high-intensity efforts (e.g., high-speed running, sprinting) constitute approximately 10% of the total distance covered (Andrzejewski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At present, elite football players travel 9 to 14 km in total during a game with high-intensity running accounting for 5–15% of this distance [ 4 , 5 , 6 ]. These performances vary according to the different playing positions of the players in the game [ 7 , 8 , 9 ]. Specifically, central midfielders cover the highest overall distance in official football games, while external players (i.e., wingers and fullbacks) cover the greatest distance in terms of high-intensity running [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%